Hoax dan Bahaya Penggunaan Media Sosial Bagi Remaja di Bali Terhadap Citra Wilayah - Ilham Prisgunanto; Syafruddin (Jurnal Pengabdian Kepada Masyarakat Kalam, 2023)
Bali is a well-known tourist destination in Indonesia which has become a concern after bad narratives circulated from recent social media posts through the attitude of foreign tourists who commit real criminal acts. This is a highlight of the Balinese people's understanding of the use of social media, especially in addressing hoax cases. Community service activities want to see an understanding of the use of social media and hoax issues there. When socialization was carried out in a number of places such as security posts, traditional villages and schools, their understanding of social media was minimal from a legal standpoint. Counseling on social media and hoax issues is provided by providing an understanding of the legality of existing laws with the existence of the Press Law and ITE Law which are the basis for prosecution. After counseling, the community service participants understand and fully understand the dangers of creating content that is dangerous for security and order.